Respuesta :
Answer:
Step-by-step explanation:
we will set up two equations:
let c be candy
let m be mints
3c+2m=10.80
c+3m=5.35, c=5.35-3m
3(5.35-3m)+2p=10.80
c=3.10
m=0.75
Let x be the cost of candy per pound and y be the cost of mint per pound.
[tex]\left \{ {{3x + 2y = 10.80} \atop {{x + 3y = 5.35}} \right.[/tex]
Rewrite the second equation for substitution:
x = 5.35 - 3y
Substitute the equation above into the first equation:
3(5.35 - 3y) + 2y = 10.80
16.05 - 9y + 2y = 10.80
-7y = -5.25
7y = 5.25
y = 0.75
∴ The price of mint per pound is $0.75.